Durability of an epoxy adhesive and a CFRP laminate under different exposure conditions - Fernandes, Pedro Miguel Gomes (2015)
In many of the retrofitted structures, carbon fibre reinforced polymer (CFRP) laminates bonded with epoxy adhesives are used. In the last decades the developed extensive research was mostly devoted to the short-term structural performance of strengthened structural elements and rarely considered the full structure’s life time. The assessment of the full structure’s life time requires the evaluation of the durability of the involved materials. The present work aims to contribute for the knowledge on the durability of a specific CFRP laminate strip and an epoxy adhesive widely used in this context. For that purpose an experimental program was carried out to assess the degradation on their tensile properties due to five distinct environments: (i) thermal cycles; (ii) freeze-thaw cycles; (iii) immersion in pure water; (iv) immersion in salt water; and, (v) wet-dry cycles with salt water. The obtained results indicate that the immersion in pure water was the most critical environment for the adhesive specimens, with a reduction on the strength of 38% after 2 years of exposure. Results also showed that the CFRP samples had negligible losses on their tensile properties.